Advanced WiMAX simulator with optimal downlink bursts construction - Abbas, Nadine Fawaz (2011)
As technology is advancing, and the internet becoming more vital, the need for faster means of communication is becoming a must. WiMAX networks are being studied to achieve different efficiency objectives. As in any communication system, high energy efficiency in WiMAX systems should be maintained by increasing resource efficiency. Thus, WiMAX resources should be properly utilized by optimizing the construction of downlink bursts. This thesis proposes an energy-efficient scheme that maximizes the use of resources at the base station by reducing the energy wasted caused by sending padding bits instead of useful data. The problem was formulated as nonlinear integer programming model. The results show an improvement in data packing that maximizes the utilization of frames and minimizes energy and resource wastage.--Furthermore, a WIMAX simulator is needed to study the Quality of Service (QoS) for WiMAX network. In the thesis, a comprehensive WiMAX simulator is proposed to measure a WiMAX network QoS, evaluate the performance of the WiMAX communication system, and aid in WiMAX network planning. The key parts of the simulator system are described including traffic generation model, Medium Access Control (MAC) layer, Physical (PHY) layer, resource allocation and frame construction. Several experiments are conducted. The results show the scalability of the system as it can support a large number of users while showing the real-life representation of the traffic models. The high accuracy of the simulator is shown by comparing the simulator results to theoretical expected values.